Three-Carbon Linked Dihydroartemisinin-Isatin Hybrids: Design, Synthesis and Their Antiproliferative Anticancer Activity - Dong, Min; Zheng, Guili; Gao, Feng; Li, Min; Zhong, Chen (Frontiers in Pharmacology, 2022)
In this study, fifteen dihydroartemisinin-isatin hybrids (5a-e and 6a-j) linked with three-carbon were designed, synthesized. The antiproliferative activity against lung cancer cell lines including drug-sensitive A549, doxorubicin-resistant A549 (A549/DOX) and cisplatin-resistant A549 (A549/DDP) lung cancer cell lines was tested. The cytotocivity towards normal lung epithelial BEAS-2B cell line was also investigated. From the structure-activity relationship (SAR), it was found that hydrogen bond donors (especially hydroxime and thiosemicarbazide) at C-3 position and electron-withdrawing groups (fluoro and chloro) at C-5 position of isatin moiety were beneficial for the activity. A significant part of them (half maximal inhibitory concentration/IC50: 5.72-55.52 μM) demonstrated considerable antiproliferative activity, and the activity was superior to that of dihydroartemisinin (IC50: 69.42-88.03 μM) and artemisinin (IC50: >100 μM). In particular, two hybrids 6a, e (IC50: 5.72-9.84 μM) were not inferior to doxorubicin (IC50: 4.06 μM) and cisplatin (IC50: 9.38 μM) against drug-sensitive A549 cells and were more potent than doxorubicin (IC50: 54.32 and 15.10 μM) and cisplatin (IC50: 19.74 and 66.89 μM) against multidrug-resistant A549/DOX and A549/DDP lung cancer cell lines. In addition, hybrids 6a, e (IC50: >100 μM) showed no toxicity towards BEAS-2B cells, proving their excellent selectivity profile. Furthermore, hybrid 6a also possessed good stability in mouse and human microsomes, as well as excellent pharmacokinetic properties. Accordingly, hybrid 6a could serve as a promising anti-lung cancer chemotherapeutic candidate for further preclinical evaluations.